P612 The use of physical restraints on children: a re-evaluation after a decade. (June 2019) - Esenay, Figen Işık; Sezer, Aslı Tufan; Demir, Ayten
Abstract : Backround: Physical restraint (PR), although controversial, is perceived as necessary for safe medical procedures. But also, this practice has important physical, psychological, social, ethical, legal and human rights consequences. In Turkey, pediatric nurses have been shown to use the restriction frequently. Aim: This study aimed to re-evaluate Turkish pediatric nurses' views and attitudes towards physical constraints after a decade. Method: This descriptive and cross-sectional study was carried out in two major hospitals in a capital city of Turkey between June-December 2018. The sample of the study consisted of pediatric units of 2 hospitals where the previous study was performed. All pediatric nurses were included in the study. A questionnaire based on to the previous study was used (Demir, 2007). The questionnairre consisted of two sections: pediatric nurses demographics and ideas and attitudes towards PR, the consent obtained, PR types used and complications. Findings: According to the study, nurses applied physical restraint to an average of 3.21 patients over the past week. This rate is lower than the previous study and this difference is statistically significant (p<0.05). The most commonly used PR methods in 2007 and 2018 are wrist (96.7%; 44.9%), ankle (81%; 28.8%), chest restraint by sheet (14%; 7, 6%), respectively. There has also been a significant decrease in the rate of PR-related complications in parallel to the decrease in PR application rates and increased awareness of patient safety (2, 3% and 23, 2%, respectively). In the previous study, none of the nurses had received written or verbal consent from children or parents, while in the current study, 19.7% of nurses reported that they received consent from the child or their parents. In 2018, education and clinics are still associated with higher PR rates. It was determined that there is still no PR procedure in most of the pediatric clinics (100% and 50, 7% in 2007 and 2018, respectively). 83, 3% of nurses reported that nurse shortages were the main reason for increased PR usage. Conclusion: Although there is a decrease in the rate of usage of physical restraints by Turkish pediatric nurses, important issues such as obtaining informed consent, informing and establishing protocols related to PR are still not at the desired level. Actions are needed to reduce the use and complications of physical restrictions including the attention of nurse staffing and education on the use of restrictions.